A 10 nm Asymmetric Graphene–Rhenium Disulfide Field‐Effect Transistor for High‐Speed Application. Issue 2 (19th December 2019) - Chawla, Rashmi; Singhal, Poonam; Garg, Amit Kumar
Abstract : Field‐effect transistor devices with exfoliated 2D materials are potent in various optical and electronics applications including photodetectors, valleytronics, spintronic, circuits, memory, and optical modulators. However, these devices endure limited gate control, low carrier mobility, and high operating voltage. This study introduces a new asymmetric graphene–rhenium disulfide heterojunction Schottky barrier metal–oxide–semiconductor field‐effect transistor engineered with high graphene carrier mobility and high rhenium disulfide I on–off ratio in a 10 nm channel‐length device. The proposed device has better gate control ability, I on–off ratio of 10 6, high carrier mobility (87.44 cm 2 V −1 s −1 ), and low subthreshold swing of 43.12 mV dec −1 in the subthreshold region at 0.05 V applied drain voltage. The significant reduction in subthreshold swing at low voltage opens a suite of high‐switching‐speed low‐powered nanologic applications for the upcoming Internet‐of‐Things era. The material properties of graphene–rhenium disulfide heterojunctions are derived using an ab initio quantum transport simulation tool. Abstract : This study introduces a asymmetric graphene–rhenium disulfide heterojunction Schottky barrier metal–oxide–semiconductor field‐effect transistor with high graphene carrier mobility and high rhenium–disulfide I on–off ratio in a 10 nm channel‐length device. The proposed device has better gate control ability, I on–off ratio (10) 6, high carrier mobility (87.44 cm 2 V −1 s −1 ), and low subthreshold swing (43.12 mV dec −1 ) in the subthreshold region at 0.05 V applied drain voltage.